The role of social media in science - Hendy, Shaun (New Zealand Science Review, 2015)
​I first started blogging on the Science Media Centre’s platform Sciblogs.co.nz in 2009, with a blog called ‘A Measure of Sci-ence’. I have found that many scientists are curious about why I blog. Who reads it? How do I find the time? Sometimes I hear comments such as, ‘Shouldn’t scientists be focussed on writing academic papers and not wasting time on social media?’ Yet in many ways, participating in social media has had a very positive impact on my career.